Comparative Evaluation of The Effect of Calcium Hydroxide and Herbal Intracanal Medicaments on The Microhardness of Radicular Dentin: An In Vitro Study - Kadu, Purva; Gulve, Meenal; Kolhe, Swapnil; Patel, Surbhi; Pawar, Pawan; Borse, Shraddha (Journal of Neonatal Surgery, 2025)
Aims: The aim of the study was to evaluate the effect of calcium hydroxide and herbal intracanal medicaments on the microhardness of radicular dentin. Methods and material: Forty freshly extracted human mandibular single rooted premolars were collected for this study. The teeth were cleaned of any debris and calculus were stored in normal saline. The teeth were decoronated at cemento-enamel junction using low speed diamond disc with mounted on straight handpiece under water cooling. Each root was sectioned longitudinally separating each root into buccal and lingual segments. Thus 80 specimens were obtained. After this exposed dentinal surface of the specimens were polished using abrasive paper. Then the segments were sectioned horizontally to obtain 3mm mid root section. The root segment was then horizontally embedded in autopolymerizing acrylic resin, leaving their dentin exposed. 80 specimens were divided into four groups. Group I (n=20): Calcium Hydroxide paste, Group II (n=20): Turmeric paste, Group III (n=20): Aloe vera gel, Group IV (n=20): Control Group. Medicament were applied on the exposed dentin. The specimens were stored in airtight containers with their respective medicaments for 2 weeks. Microhardness was measured using a Vicker’s microhardness tester with a 50-g load for 10 seconds on the polished surface. Statistical analysis used: Data obtained was entered and sorted in Microsoft Excel (v.2010). Statistical analysis was performed using Statistical package for social sciences (SPSS) software (v.21.0). Descriptive quantitative data was expressed in mean and standard deviation respectively. Data normality was checked by using Shapiro – Wilk test. Results: Mean microhardness value Group IV> Group III> Group II> Group I Conclusion: This study found that calcium hydroxide significantly reduced radicular dentin microhardness more than turmeric paste, aloe vera gel, and the control group. While turmeric paste and aloe vera gel similarly decreased microhardness, only turmeric showed a significant reduction compared to the control group. Aloe vera gel also reduced microhardness, but the difference was not statistically significant.